Perceived Preparedness of Dental Academic Institutions to Cope with the COVID-19 Pandemic: A Multi-Country Survey. - Ammar, Nour; Aly, Nourhan M; Folayan, Morenike Oluwatoyin; Khader, Yousef; Mohebbi, Simin Z; Attia, Sameh; Howaldt, Hans-Peter; Boettger, Sebastian; Virtanen, Jorma; Madi, Marwa; Maharani, Diah A; Rahardjo, Anton; et al. (MDPI, 2024)
15p.